Canine Chronic Kidney Disease (CKD): Insights into Diagnosis, Management and Prognosis in Pit Bull Dog: A Case Report - Mahajan, Chetna; Priyanka; Gupta, Kapil; Bhardwaz, Anavil; Singh, Inderpal (International Journal of Bio-resource and Stress Management, 2025)
The Study was conducted from June to July, 2023 at Teaching Veterinary Clinical Complex Rampura Phul, Bathinda, Punjab, India to study the overview of CKD in dogs, including its etiology, clinical presentation, diagnostic approach, management strategies, and prognostic factors. A male Pit bull dog, aged five and a half years, weighing 14.5 kg was presented with deteriorating body condition, pale gums, lethargy, weakness, fever, and low appetite. Laboratory tests such as serum chemistry (e.g., creatinine, blood urea nitrogen), urinalysis (e.g., proteinuria, urine specific gravity), and imaging studies (e.g., ultrasound) were done. Elevated levels of BUN, Creatinine, Potassium and proteinurea were suggestive of CKD. Further, the kidney lacked cortico-medullary differentiation. Urinary bladder concretions were also observed on USG examination. These alterations confirmed cholecystitis or chronic kidney disease. The objective of study was to manage CKD in the patient which aimed to halt the spread of the illness, reduce symptoms and improve quality of life through dietary modifications (e.g., low phosphorus, high-quality protein), medications and fluid therapy to restore electrolyte balance. As a result of regular monitoring of clinical signs, renal function, treatment and follow up for 2 months azotaemia was resolved to quite extent with restoration of blood urea nitrogen and creatinine upto normal reference level and improvement of dog was also evident by normal physical activity, diet intake and playful behaviour.